Generation of a USP9Y knockout human embryonic stem cell line with CRISPR-Cas9 technology - Sai Wei; Yuting Zhen; Chao Sun; Yanlin Ma; Qi Li; Luan Wen (Stem Cell Research)
Human embryonic stem cell (hESC) lines are vital tools for studying gene function, disease modeling, and therapy. We generated a USP9Y knockout hESC line using CRISPR-Cas9 in the male-derived H1 line. Targeted deletion of the USP9Y gene was confirmed via PCR and sequencing. The modified line retained pluripotency markers, exhibited a normal karyotype, and differentiated into all three germ layers. This model provides a valuable platform for studying USP9Y’s role in human development and male infertility, offering insights into related disorders and therapeutic potential.